Star Wars. Scoundrels - Zahn, Timothy (Del Rey/Ballantine Books, 2012)
Han Solo, Chewbacca, and Lando Calrissian work together on a potentially lucrative heist in the hopes of paying of Jabba the Hutt's bounty on Han's head.